Thrombin-derived host defence peptide modulates neutrophil rolling and migration in vitro and functional response in vivo - Lim, Chun Hwee (2017)
Host defence peptides (HDPs) derived from the C-terminus of thrombin are proteolytically generated by enzymes released during inflammation and wounding. In this work, we studied the effects of the prototypic peptide GKY25 (GKYGFYTHVFRLKKWIQKVIDQFGE), on neutrophil functions. In vitro, GKY25 was shown to decrease LPS-induced neutrophil activation. In addition, the peptide induced CD62L shedding on neutrophils without inducing their activation. Correspondingly, GKY25-treated neutrophils showed reduced attachment and rolling behaviour on surfaces coated with the CD62L ligand E-selectin. The GKY25-treated neutrophils also displayed a dampened chemotactic response against the chemokine IL-8. Furthermore, in vivo, mice treated with GKY25 exhibited a reduced local ROS response against LPS. Taken together, our results show that GKY25 can modulate neutrophil functions in vitro and in vivo.